2021
DOI: 10.1002/mrm.28746
|View full text |Cite
|
Sign up to set email alerts
|

Aliasing artifact reduction in spiral real‐time MRI

Abstract: Purpose: To mitigate a common artifact in spiral real-time MRI, caused by aliasing of signal outside the desired FOV. This artifact frequently occurs in midsagittal speech real-time MRI. Methods: Simulations were performed to determine the likely origin of the artifact.Two methods to mitigate the artifact are proposed. The first approach, denoted as "large FOV" (LF), keeps an FOV that is large enough to include the artifact signal source during reconstruction. The second approach, denoted as "estimationsubtrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…During RT‐MRI acquisition, each spiral OIOI trajectory is rotated with golden angle (111.25°) after each TR, which benefits constrained reconstruction 25 and allows for flexible selection of the reconstruction FOV and temporal resolution 26,27 . Reconstruction FOV was selected to include all signal area to avoid spiral aliasing artifact 28 . We report both the FOV during the single spiral‐out trajectory design and the FOV used for image reconstruction in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During RT‐MRI acquisition, each spiral OIOI trajectory is rotated with golden angle (111.25°) after each TR, which benefits constrained reconstruction 25 and allows for flexible selection of the reconstruction FOV and temporal resolution 26,27 . Reconstruction FOV was selected to include all signal area to avoid spiral aliasing artifact 28 . We report both the FOV during the single spiral‐out trajectory design and the FOV used for image reconstruction in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 Reconstruction FOV was selected to include all signal area to avoid spiral aliasing artifact. 28 We report both the FOV during the single spiral-out trajectory design and the FOV used for image reconstruction in Table S1.…”
Section: Spiral Oioi Trajectory Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐Cartesian trajectories that can resolve the spectra have been explored, such as by Franson et al, who demonstrated a rosette trajectory, 83 and Tian et al, who proposed a novel multi‐echo spiral acquisition 84 . Both these trajectories demonstrated good fat‐water separation using relatively long TRs (10–12 msec) possible with bSSFP at 0.55 T.…”
Section: Routine Cardiac Mri Sequences At Lower Fieldmentioning
confidence: 99%
“…In the past few decades, optimization problem has been a hot issue, and scholars have proposed many optimization algorithms for this problem. However, in most of the previous research works on optimization problem, the objective function of the problem is usually assumed to be time‐invariant, but in practical applications, there are many time‐varying optimization problems, such as robot, 1 resource allocation, 2 communications, 3 signal processing, 4 medical engineering 5 . In order to solve such problems, it is necessary to propose some time‐varying optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%